Prevalence, knowledge and attitude toward electronic cigarette use among male health colleges students in Saudi Arabia—A cross-sectional study - Alsanea, Sary; Alrabiah, Ziyad; Samreen, Sana; Syed, Wajid; Bin Khunayn, Rawan M.; Al-Arifi, Nasser M.; Alenazi, Miteb; Alghadeer, Sultan; Alhossan, Abdulaziz; Alwhaibi, Abdulrahman; Al-Arifi, Mohamed N. (Frontiers in Public Health, 2022)
Background Health care professionals have an important role in increasing awareness about smoking harms and serving as role models. This study aims to assess knowledge, attitude and perception toward electronic cigarettes (ECs) as well as prevalence of ECs use among male health colleges students. Method This is a cross-sectional survey-based study conducted among students in the male campus of five different health colleges over a 4-month period from February 2020 to May 2020. Descriptive analysis was used to assess the knowledge, perception and attitude, and inferential testing was used to evaluate the association of different participant's variables and knowledge toward ECs usage using SPSS. Results A total of 333 students were included in the analysis. Most of students (n = 205; 61.6%) had never used ECs, while 22.8 and 15.6% used them for recreational and smoking cessation purposes, respectively. Focusing on ECs users from each college individually, medical students had the highest prevalence followed by dental, pharmacy and nursing students (47.4, 40.7, 34.5, and 32%, respectively). Many students had misconceptions and a low level of knowledge about ECs, such as recognizing them as smoking-cessation tools and not knowing whether toxic and carcinogenic components levels in ECs are similar to conventional cigarettes, respectively. Medical students had significantly higher knowledge compared to dental students [3 (2) vs. 2 (1); p = 0.033]. Moreover, smokers were less knowledgeable than non-smokers [2.5 (1) vs. 2.1 (1), p = 0.027]. At least 62.8% of students perceived using ECs as a fashionable alternative smoking method and 59.2% believed that they may become a gateway for smoking addiction. Only 120 (36.0%) health colleges students were confidently able to advise smokers regarding ECs. Conclusion Our study highlights an increased trend of ECs use accompanied with insufficient knowledge and several misconceptions about ECs among health colleges students. This was associated with a negative influence on their attitude toward ECs use, which would potentially lead to negative consequences on public health.